The behavior of the Bacillus probiotic species under conditions of co-cultivation - O. V. Knysh; A. V. Martynov; S. I. Pokhyl; N. I. Skliar (Сучасні медичні технології)
Combining probiotic bacteria is a promising strategy to increase the effectiveness and avoid side effects of probiotic therapy. Bacteria that find themselves in a common environment are able to both change their properties and show new ones under the influence of each other. The change of colonization and antagonistic properties, which provide bacteria with competitive advantages in the development of new spaces, deserves special attention.